Features and functionality of speed and power capabilities of elite climbers and various types of rock climbing - Ryepko, O. A. (Physical Education of Students, 2013)
The purpose of this study was comparative and functional characterization of speed- force readiness elite athletes - representatives of climbing to the complexity, speed and climbers. The study involved 26 athletes: 10 masters of sports of international class (speed climbing), 10 masters of sports of international class (climbing difficulty), 6 world-class climbers. The age of the athletes was 19-22 years. Found that the different types of rock climbing have different requirements for the development of the components of speed- force readiness: speed climbing is more conducive to the development of explosive power and speed endurance, climbing on the complexity is more conducive to the development of power abilities and strength endurance in short time intervals. Taken in the study to compare climbing contributes to the development of strength endurance over longer intervals of time.